2017
DOI: 10.1016/j.bmcl.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Novel small molecule guanidine Sigma1 inhibitors for advanced prostate cancer

Abstract: Prostate cancer is the most frequently diagnosed malignancy and the leading cause of cancer related death in men. First line therapy for disseminated disease relies on androgen deprivation, leveraging the addiction of these tumors on androgens for both growth and survival. Treatment typically involves antagonizing the androgen receptor (AR) or blocking the synthesis of androgens. Recurrence is common and within 2–3 years patients develop castration resistant tumors that become unresponsive to AR-axis targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…A aplicação da radiação de micro-ondas em reações orgânicas apresenta destaque na literatura, visto que seu uso em sínteses orgânicas demostra que em uma menor quantidade de tempo, com presença ou ausência de solventes, é possível melhorar rendimentos e até mesmo realizar sínteses que antes não eram possíveis. 40,41 Com esse enfoque, melhor rendimento, menor tempo reacional e, principalmente o respeito ao sexto protocolo da química verde: Eficiência energética, esta proposta metodológica foi desenvolvida em reator de micro-ondas, sem agentes tiofílicos, sem solventes, sem refluxo, com este objetivo.…”
Section: Metodologia C -Reação De Guanilação Da Tioureia 8 Sem Agente...unclassified
“…A aplicação da radiação de micro-ondas em reações orgânicas apresenta destaque na literatura, visto que seu uso em sínteses orgânicas demostra que em uma menor quantidade de tempo, com presença ou ausência de solventes, é possível melhorar rendimentos e até mesmo realizar sínteses que antes não eram possíveis. 40,41 Com esse enfoque, melhor rendimento, menor tempo reacional e, principalmente o respeito ao sexto protocolo da química verde: Eficiência energética, esta proposta metodológica foi desenvolvida em reator de micro-ondas, sem agentes tiofílicos, sem solventes, sem refluxo, com este objetivo.…”
Section: Metodologia C -Reação De Guanilação Da Tioureia 8 Sem Agente...unclassified
“…The active site of these target proteins comprises one or more acidic amino acids. Recent studies have shown that guanidine-based drugs specifically bind to acidic residues present at the active site of an enzyme via hydrogen-bond interactions. Crystal structures of the avian flu neuraminidase inhibitor zanamivir show the inhibitor molecule bridging the active site residues Asp152 and Glu229 . Understanding the pH-dependent binding of guanidine-based drug molecules to proteins can aid in designing better drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that guanidine-based drugs specifically bind to acidic residues present at the active site of an enzyme via hydrogen-bonded interactions. 4042 Crystal structures of the avian flu neuraminidase inhibitor zanamivir show the inhibitor molecule bridging the active site residues Asp152 and Glu229. 43…”
Section: Introductionmentioning
confidence: 99%